X-ray absorption spectroscopy at the sulfur K-edge: A new tool to investigate the biochemical mechanisms of neurodegeneration - Hackett, Mark; Smith, S.; Paterson, P.; Nichol, H.; Pickering, I.; George, G. (American Chemical Society, 2012)
Sulfur containing molecules such as thiols, disulfides, sulfoxides, sulfonic acids, and sulfates may contribute to neurodegenerative processes. However, previous study in this field has been limited by the lack of in situ analytical techniques. This limitation may now be largely overcome following the development of synchrotron radiation X-ray absorption spectroscopy at the sulfur K-edge, which has been validated as a novel tool to investigate and image the speciation of sulfur in situ. In this investigation, we build the foundation required for future application of this technique to study and image the speciation of sulfur in situ within brain tissue. This study has determined the effect of sample preparation and fixation methods on the speciation of sulfur in thin sections of rat brain tissue, determined the speciation of sulfur within specific brain regions (brain stem and cerebellum), and identified sulfur specific markers of peroxidative stress following metal catalyzed reactive oxygen species production. X-ray absorption spectroscopy at the sulfur K-edge is now poised for an exciting new range of applications to study thiol redox, methionine oxidation, and the role of taurine and sulfatides during neurodegeneration. © 2012 American Chemical Society.